Über ikonische Beweise in der Mathematik : Summen von Quadraten in der Zahlentheorie (mathematica didactica, 2021)
The article is focusing on iconic proofs in mathematics. In particular, number theoretical examples of the representation of integers as sums of squares are discussed and ideas for the integration into school education and higher education are given. Hereby, the collection of so called “Proofs without Words” of Roger B. Nelsen can be considered as basis. Those illustrations may be used in school as well as for higher education teaching at an early stage of mathematical reasoning.